Association of Angiotensin-Converting Enzyme Inhibitor or Angiotensin Receptor Blocker Use With COVID-19 Diagnosis and Mortality - Fosbøl, Emil L; Butt, Jawad H; Østergaard, Lauge; Andersson, Charlotte; Selmer, Christian; Kragholm, Kristian; Schou, Morten; Phelps, Matthew; Gislason, Gunnar H; Gerds, Thomas A; Torp-Pedersen, Christian; Køber, Lars (JAMA : the journal of the American Medical Association, 2020)
It has been hypothesized that angiotensin-converting enzyme inhibitors (ACEIs)/angiotensin receptor blockers (ARBs) may make patients more susceptible to coronavirus disease 2019 (COVID-19) and to worse outcomes through upregulation of the functional receptor of the virus, angiotensin-converting enzyme 2. To examine whether use of ACEI/ARBs was associated with COVID-19 diagnosis and worse outcomes in patients with COVID-19. To examine outcomes among patients with COVID-19, a retrospective cohort study using data from Danish national administrative registries was conducted. Patients with COVID-19 from February 22 to May 4, 2020, were identified using ICD-10 codes and followed up from day of diagnosis to outcome or end of study period (May 4, 2020). To examine susceptibility to COVID-19, a Cox regression model with a nested case-control framework was used to examine the association between use of ACEI/ARBs vs other antihypertensive drugs and the incidence rate of a COVID-19 diagnosis in a cohort of patients with hypertension from February 1 to May 4, 2020. ACEI/ARB use was defined as prescription fillings 6 months prior to the index date. In the retrospective cohort study, the primary outcome was death, and a secondary outcome was a composite outcome of death or severe COVID-19. In the nested case-control susceptibility analysis, the outcome was COVID-19 diagnosis. In the retrospective cohort study, 4480 patients with COVID-19 were included (median age, 54.7 years [interquartile range, 40.9-72.0]; 47.9% men). There were 895 users (20.0%) of ACEI/ARBs and 3585 nonusers (80.0%). In the ACEI/ARB group, 18.1% died within 30 days vs 7.3% in the nonuser group, but this association was not significant after adjustment for age, sex, and medical history (adjusted hazard ratio [HR], 0.83 [95% CI, 0.67-1.03]). Death or severe COVID-19 occurred in 31.9% of ACEI/ARB users vs 14.2% of nonusers by 30 days (adjusted HR, 1.04 [95% CI, 0.89-1.23]). In the nested case-control analysis of COVID-19 susceptibility, 571 patients with COVID-19 and prior hypertension (median age, 73.9 years; 54.3% men) were compared with 5710 age- and sex-matched controls with prior hypertension but not COVID-19. Among those with COVID-19, 86.5% used ACEI/ARBs vs 85.4% of controls; ACEI/ARB use compared with other antihypertensive drugs was not significantly associated with higher incidence of COVID-19 (adjusted HR, 1.05 [95% CI, 0.80-1.36]). Prior use of ACEI/ARBs was not significantly associated with COVID-19 diagnosis among patients with hypertension or with mortality or severe disease among patients diagnosed as having COVID-19. These findings do not support discontinuation of ACEI/ARB medications that are clinically indicated in the context of the COVID-19 pandemic.